Sustainable Tourism and Destination Brand Loyalty: Exploring the Roles of Brand Equity and Tourist Satisfaction in Bali - Khrisna Triharyo (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Bali, as one of Indonesia's most prominent tourist destinations, is currently facing the challenges of overtourism, which threatens its long-term sustainability. Sustainable Tourism Practices (STP) have been introduced as a means to mitigate these negative impacts while ensuring continued tourism appeal. This study examines the relationship between Sustainable Tourism Practices (STP) and Customer Satisfaction using the Expectancy-Disconfirmation Model (EDM) as the theoretical foundation. While previous research has explored the direct link between STP and satisfaction, this study identifies a theoretical gap by incorporating EDM to explain how expectations formed by sustainable initiatives influence customer perceptions. The research aims to assess the impact of STP across four dimensions: environmental, economic, socio-cultural, and institutional on customer satisfaction in a tourism context. A quantitative approach is employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected through a structured questionnaire. 200 datasets are obtained from the tourists who recently visited Bali from 2023-2025 and analyzed through inner, outer model analyses as well as hypotheses testing using bootstrapping analysis. It is statistically proven that brand image and tourist satisfaction mediated the impact of four dimensions of sustainable tourism practices on brand loyalty with socio-cultural dimension exhibits the biggest effect. As the managerial implications of this resarch, it is suggested to Bali Tourism Board to initiate some campaigns in order to promote more about sustainable tourism practices in Bali as the effort that would lead into having robust brand equity as the key-driver of having satisfied and loyal tourists.